Hydrogeochemical and Biogeochemical Processes in Kaffiøyra River Catchments (Spitsbergen, Norway) - Borysiak Janina; Grześ Marek; Pulina Marian; Szpikowska Grażyna (Quaestiones Geographicae, 2015)
The paper presents the results of hydrogeochemical and biogeochemical studies in the area of Kaffiøyra river catchments in the ablation season 2004. Vegetation, hydrological regime, mineralization and ionic composition of circulating waters, rate of annual chemical denudation and biogenic CO2 content in soil air in relation to the concentration of dissolved and transported HCO3 - ions were documented. The waters represented the type HCO3 - - SO42- - Ca2+ - Mg2+. Most of ions showed a good correlation with electrical conductivity. A good correlation between dissolved and transported mass and the discharge was shown. The value of the chemical denudation in non-glacierized catchments of the Kaffiøyra plain was 0.07 and 0.13 t km-2 d-1, in glacierized catchment - 0,21 t km-2 d-1. The biogenic CO2 concentrations in tundra soil air ranged from 0.03-0.08%, while the average was 0.046%. The mean rate of CO2 ionic transport was 3 kg d-1, while of HCO3 - - 0.63 t d-1. A low correlation between the concentration of biogenic CO2 in soil air and HCO3 - was found, which indicates the involvement of other, unexamined bio- and physico-chemical processes.